O espaço agrário de Ponte de Lima : alguns contrastes - Pina, Maria Helena Mesquita (1990)
The present council area of Ponte de Lima, resulting from a turbulent history until the 16th century, only experienced growth in its economic activity from the 17th century onwards. And yet by the second half of the 20th century its economy was based essentially on an agroflorestal sector, supported by a most inadequate agrarian structure and by an aged population with a low level of learning and of technical instruction. It was only after the 1960s that the economic structure of this council area began to transform with greater diversification and specialization. However, the traditional entity of the family structure still dominates and technical equipment and professional training are almost inexistent. On the other hand, the spatial asymmetry which has been detected becomes ever more pronounced; at the end of the 1980s we are thus presented with a morphological, economic and socially contrasting domination, whatever the information which this analysis might be based upon and the technique of statistical treatment which might be used, as this article shows.